(untitled) (Papeles, 2025)
Introduction: The implementation of Outcome-Based Education (OBE) in vocational education aims to align learning outcomes with specific industry demands, ensuring that graduates possess the skills required for the modern workforce. This study examines OBE’s role in advancing vocational education in Indonesia by addressing key aspects such as curriculum design, teacher preparedness, and infrastructural support. Methodology: A qualitative literature review was conducted, analyzing academic articles, government regulations, and case studies related to OBE in vocational settings. This review synthesizes insights into critical implementation strategies, potential benefits, and recurring challenges with the aim of building a detailed understanding of OBE’s impact. Results and discussion: The findings reveal that OBE significantly improves the alignment between vocational education curricula and industry needs, enhancing both technical expertise and essential soft skills. Initiatives like Teaching Factory illustrate OBE’s practical advantages. However, challenges persist in areas such as teacher training, limited resources, and the complexity of evaluation mechanisms. Addressing these issues is crucial for sustainable and effective implementation. Conclusions: OBE holds transformative potential for vocational education by promoting curriculum flexibility and graduate readiness. Achieving this potential requires continuous investment in teacher development, infrastructure enhancement, and strengthened industry collaborations. These findings offer valuable insights for educators and policymakers who aim to refine OBE practices and frameworks to meet workforce demands.